Ultrasound definition of tendon damage in patients with rheumatoid arthritis. Results of a OMERACT consensus-based ultrasound score focussing on the diagnostic reliability. Issue 11 (12th August 2013) - Bruyn, George A W; Hanova, Petra; Iagnocco, Annamaria; d'Agostino, Maria-Antonietta; Möller, Ingrid; Terslev, Lene; Backhaus, Marina; Balint, Peter V; Filippucci, Emilio; Baudoin, Paul; van Vugt, Richard; Pineda, Carlos; et al.
Abstract : Objective: To develop the first ultrasound scoring system of tendon damage in rheumatoid arthritis (RA) and assess its intraobserver and interobserver reliability. Methods: We conducted a Delphi study on ultrasound-defined tendon damage and ultrasound scoring system of tendon damage in RA among 35 international rheumatologists with experience in musculoskeletal ultrasound. Twelve patients with RA were included and assessed twice by 12 rheumatologists-sonographers. Ultrasound examination for tendon damage in B mode of five wrist extensor compartments (extensor carpi radialis brevis and longus; extensor pollicis longus; extensor digitorum communis; extensor digiti minimi; extensor carpi ulnaris) and one ankle tendon (tibialis posterior) was performed blindly, independently and bilaterally in each patient. Intraobserver and interobserver reliability were calculated by κ coefficients. Results: A three-grade semiquantitative scoring system was agreed for scoring tendon damage in B mode. The mean intraobserver reliability for tendon damage scoring was excellent (κ value 0.91). The mean interobserver reliability assessment showed good κ values (κ value 0.75). The most reliable were the extensor digiti minimi, the extensor carpi ulnaris, and the tibialis posterior tendons. An ultrasound reference image atlas of tenosynovitis and tendon damage was also developed. Conclusions: Ultrasound is a reproducible tool for evaluating tendon damage in RA. This study strongly supports a new reliable ultrasound scoring system for tendon damage.